Pengaruh Independensi, Pengalaman Kerja Dan Kompetensi Terhadap Kinerja Auditor Internal Pada Bank Perkreditan Rakyat (BPR) Di Kota Denpasar - Ni Putu Delia Trisna Pratami; Ni Made Wisni Arie Pramuki; Ni Putu Yeni Yuliantari (Hita Akuntansi dan Keuangan, 2025)
The presence of Rural Banks (BPR) in Indonesia greatly benefits local communities by providing much-needed capital for their businesses, thereby supporting the government's efforts to accelerate economic development. However, the high number of bankruptcies among BPRs, often due to internal fraud, highlights the poor performance of internal auditors responsible for overseeing and examining bank operations. This study aims to examine the impact of independence, work experience, and competence on the performance of internal auditors at Rural Banks in Denpasar City. The research involved all internal auditors from 23 BPRs headquartered in Denpasar, totaling 38 respondents, selected through a saturated sampling technique. Data were collected via questionnaires and analyzed using the Partial Least Squares (PLS) method. The findings reveal that both independence and work experience significantly and positively influence the performance of internal auditors at BPRs in Denpasar City. However, competence has an insignificant negative impact on their performance.